CEU Opening Ceremony, 10th Anniversary (Pesti Vigadó) - Primary Camera III
Continuation of the CEU Opening Ceremony for the class of 2001/2002 held at Pesti Vigadó, Concert Hall on October 13, 2001. After Lord Russell-Johnston’s lecture, Pro-Rector of CEU, Stefan Messmann offers the closing remarks of the Ceremony. The Ceremony is followed by a Press Conference at Pesti Vigadó, where the chair is István Teplán (Executive Vice President of CEU) and the participants are George Soros (Founder of CEU and the Chairman of the Board of Trustees), Yehuda Elkana (Rector and President of CEU) and Zuzana Jalcova (PhD Student).